Follow-up in Patients With Non-invasive Prenatal Screening Failures: A Reflection on the Choice of Further Prenatal Diagnosis - Liu, Sha; Liu, Hongqian; Liu, Jianlong; Bai, Ting; Jing, Xiaosha; Xia, Tianyu; Deng, Cechuan; Liu, Yunyun; Cheng, Jing; Wei, Xiang; Xing, Lingling; Luo, Yuan; et al. (Frontiers in Genetics, 2021)
Background: Our aim was to provide a theoretical basis for clinicians to conduct genetic counseling and choose further prenatal diagnosis methods for pregnant women who failed noninvasive prenatal screening (NIPS). Methods: A retrospective analysis was performed on pregnant women who had failed NIPS tests. Results: Among the 123,291 samples, 394 pregnant women did not obtain valid results due to test failures. Total 378 pregnant women were available for follow-up, while 16 patients were lost to follow-up. Of these 378, 135 pregnant women chose further prenatal diagnosis through amniocentesis, and one case of dysplasia was recalled for postpartum chromosome testing. The incidence rate of congenital chromosomal abnormalities in those who failed the NIPS was 3.97% (15/378), which was higher than that of the chromosomal abnormalities in the common population (1.8%). Among the pregnant women who received prenatal diagnosis, the positive rates of chromosomal abnormalities in the chromosomal microarray analysis/copy number variation sequencing (CMA/CNV-seq) group and in the karyotyping group were 15.28% and 4.76%, respectively. Conclusion: Prenatal diagnosis should be strongly recommended in post-test genetic counseling for pregnant women with NIPS failures. Further, high-resolution detection methods should be recommended for additional prenatal diagnoses.